Transforaminal Epidural Steroid Injections: A Systematic Review and Meta-Analysis of Efficacy and Safety - Helm Ii, Standiford; Harmon, Preston C; Noe, Carl; Calodney, Aaron K; Abd-Elsayed, Alaa; Knezevic, Nebojsa Nick; Racz, Gabor B (Pain physician, 2021)
BACKGROUND: Transforaminal epidural injections have been used since the late 1990s to treat lumbar radicular pain. They have been the subject of considerable attention, with varying conclusions from systematic reviews as to their efficacy. Transforaminal injections have been associated with rare but major complications. Further, the use of transforaminal injections has increased since the passage of the Affordable Care Act. Finally, with the SARS-CoV-2 pandemic, there has been heightened concern regarding the risk associated with steroid injections. OBJECTIVES: To evaluate and update the effectiveness of transforaminal injections for 4 indications: radicular pain; from spinal stenosis; from failed back surgery syndrome; and for axial low back pain; and to evaluate the safety of the procedure. STUDY DESIGN: A systematic review and meta-analysis of the efficacy of transforaminal injections. METHODS: The available literature on transforaminal injections was reviewed and the quality assessed. The level of evidence was classified on a 5-point scale based on the quality of evidence developed by the US Preventive Services Task Force (USPSTF) and modified by the American Society of Interventional Pain Physicians (ASIPP). Data sources included relevant literature from 1966 to April 2020, and manual searches of the bibliographies of known primary and review articles. Pain relief and functional improvement were the primary outcome measures. A minimum of 6 months pain relief follow-up was required. RESULTS: For this systematic review, 66 studies were identified. Eighteen randomized controlled trials met the inclusion criteria. No observational studies were included. Eleven randomized controlled trials dealt with various aspects of transforaminal injections for radicular pain owing to disc herniation. Based on these studies, there is Level 1 evidence supporting the use of transforaminal injections for radicular pain owing to disc herniation. A meta-analysis showed that at both 3 and 6 months, there was highly statistically significant improvement in both pain and function with both particulate and nonparticulate steroids. For radicular pain from central stenosis there is one moderate quality study, with Level IV evidence. For radicular pain caused by failed back surgery syndrome there is one moderate quality study, with Level IV evidence. For radicular pain from foraminal stenosis and for axial pain there is Level V evidence, opinion-based/consensus, supporting the use of transforaminal injections. Transforaminal injections are generally safe. However, they have been associated with major neurologic complications related to cord infarct. Causes other than intraluminal injection of particulates appear to be at play. The use of an infraneural approach and of blunt needles appear to offer the greatest patient safety. Because of concern over the role of particulate steroids, multiple other injectates have been evaluated, including nonparticulate steroids, tumor necrosis factor alpha (TNF-a) inhibitors, and local anesthetics without steroids. No injectate has been proven superior. If there is concern about immunosuppression because of risk of COVID-19 infection, either the lowest possible dose of steroid or no steroid should be used. LIMITATIONS: The study was limited by the paucity of literature for some indications. CONCLUSIONS: There is Level I evidence for the use of transforaminal injections for radicular pain from disc herniations. KEY WORDS: Disc herniation, spinal pain, radicular pain, epidural steroid injection, transforaminal injection, spinal stenosis, post lumbar surgery syndrome, axial low back pain